2017
DOI: 10.1080/10942912.2017.1344990
|View full text |Cite
|
Sign up to set email alerts
|

Stability of lactic acid bacteria in synbiotic sugared and sugar-free milk chocolates

Abstract: In this study, stability of Lactobacillus acidophilus and L. paracasei in synbiotic sugared and sugar-free milk chocolates within 90-day storage was investigated, considering inline as prebiotic. Probiotic bacteria inoculation at 9.0 log cfu/25 g and usage of inulin with Degree of Polymerisation (DP) <10 and DP > 23 at a concentration of 9.0 g/100 g were investigated. At the end of 90 days, at least 6.5 log cfu/25 g probiotic bacteria was determined in the samples containing L. acidophilus, whereas this value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…However, the number of studies related to (i) using in the compound chocolate formulation and (ii) investigating the effects of DP value on functional and technological properties of chocolate and compound chocolate are very limited. According to the results of previous studies of our research group, inulin DP has effects on the functional properties of white (Konar et al, 2018), milk (Toker et al, 2017), and dark (Konar et al, 2017) chocolates. To our knowledge, this is the first study in which the effects of inulin DP and concentrations on main quality parameters of compound chocolate were investigated.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…However, the number of studies related to (i) using in the compound chocolate formulation and (ii) investigating the effects of DP value on functional and technological properties of chocolate and compound chocolate are very limited. According to the results of previous studies of our research group, inulin DP has effects on the functional properties of white (Konar et al, 2018), milk (Toker et al, 2017), and dark (Konar et al, 2017) chocolates. To our knowledge, this is the first study in which the effects of inulin DP and concentrations on main quality parameters of compound chocolate were investigated.…”
Section: Introductionmentioning
confidence: 65%
“…According to the results of previous studies of our research group, inulin DP has effects on the functional properties of white (Konar et al, 2018), milk (Toker et al, 2017), and dark (Konar et al, 2017) chocolates. To our knowledge, this is the first study in which the effects of inulin DP and concentrations on main quality parameters of compound chocolate were investigated.…”
Section: Introductionmentioning
confidence: 78%
“…After 90 days, probiotic viability was above 6.61 log cfu/25 g which L. acidophilus showed higher levels of viability than L. paracasei. Another study within a similar group research showed that in milk chocolate, the probiotics viability was above 5.90 log cfu/25 g which L. acidophilus showed higher levels of viability than L. paracasei after 90 days storage [27]. Interestingly, Rad et al [9] reported that L. casei 431-incorporated milk chocolates could be stored at 20 °C for 6 months.…”
Section: Incorporation Of Probiotics In Chocolatementioning
confidence: 97%
“…Taking this concept a step further, synbiotic chocolate emerges as a unique and innovative product that seamlessly integrates the goodness of probiotics and prebiotics with the delightful experience of indulging in chocolate (Rouhi et al ., 2015). This novel approach involves incorporating specific probiotic strains and prebiotic components into the chocolate formulations (Mandal et al ., 2013; Toker et al ., 2017). Manufacturers, by doing so, can craft functional foods that not only deliver the satisfying taste of chocolate but also provide additional health benefits (Konar et al ., 2017).…”
Section: Current Functional Chocolate Productsmentioning
confidence: 99%